Edukasi Pencegahan dan Penguluran pada Nyeri Leher di SMA 1 Kuala Tungkal - Junaidi, Adi Saputra; Hasmar , Wanti (Prosiding Seminar Kesehatan Nasional, 2024)
Neck pain that is felt in the back of the upper or cervical spine. The pain felt can radiate to the head and shoulders and even the fingers. Neck pain is a common problem. International data in 1996 mentions 3.5% cases per 1,000 people. At least two out of three people will experience it during their lifetime.  A potential cause of neck pain is pressure on soft tissues, bones, or joints in the cervical area. In some cases it can also be caused by hyperextension trauma or whisplash injury, overuse by looking down for too long while working